Perfil dos estudantes do Curso de Medicina da Escola Multicampi de Ciências Médicas do Rio Grande do Norte/UFRN - Germano, Joelia Celeste Vieira (2017)
Significant part of Brazilian population that lives in rural or remote areas is affected by a lack of medical care, where usually there are not many professionals to assist patients of the Unified Health System (SUS). This shortage of doctors in health services is a relative concept, since the greatest problem is not in the number of doctors in Brazil, but their distribution throughout the national territory. The difficulty of providing and setting professionals in the country was the main reason for the Federal Government created the Mais Médicos Programme (PMM). In this context, the Multicampi School of Medical Sciences of the Federal University of Rio Grande do Norte (EMCM / UFRN) was created. The EMCM medical course seeks to train professionals to work effectively in the labor market, particularly in the rural context and outside the major urban centers, taking the health needs, ethical and cultural values of our population under advisement. This research aims to describe a profile of the students of the medical course of the EMCM in an attempt that the obtained information can subsidize pedagogical strategies that contribute with a better academic performance and consequently with the formation of physicians in line with the need of the SUS. The data was acquired from a questionnaire sent to all students of the first three classes of the medical course of EMCM. This research showed that most of the students are male, born in the states of Rio Grande do Norte or Paraiba, with a family income equal or less than 5 minimum wages, users of SUS and beneficiary of some inclusion policy.